Evaluation of cell biomarkers as in vitro photoprotective assays for sunscreen formulations - Sônia Aparecida Figueiredo; Fernanda Maria Pinto Vilela; Thaís Nunes dos Anjos; Amanda Natalina Faria de Pádua; Maria José Vieira Fonseca (São Paulo State University (UNESP), 2021)
Objectives: The aim of this study was to evaluate cellular indicators, which change with exposure to ultraviolet (UV) radiation and can be used as parameters for measuring sunscreens efficiency. Methods: Commercial strains of L929 and HaCaT cells (skin dermis and epidermis, respectively), from the cell bank of Rio de Janeiro, were exposed to different doses of UVA (350 nm) and UVB (309 nm) radiation. The evaluation of the photoprotective potential of sunscreens was analyzed with cell viability, lipid peroxidation and ROS generation tests. Samples of sunscreen with SPF values ranging from 15 to 60 were applied to a quartz plate superimposed on the top of a microplate containing the cell culture, and then the system was irradiated. Results: The viability and lipid peroxidation of the two cell lines remained unchanged after exposure to UVA radiation. When exposed to UVB radiation, the reduction in viability and the increase in lipid peroxides were dose-dependent, that is, they varied from 3.15% to 95.4%, and from 1.2 to 42.7 nM MDA/pg protein, respectively, both for the L929 strain. The dose of 0.5 J/cm2 reduced by 41.4%±1.67 the number of viable cells, and the dose of 30 J/cm2 promoted the oxidation of 42.7 nM of MDA/pg protein. These doses were selected to evaluate the photoprotective effectiveness of commercial sunscreens. Sunscreens exposed to UVB rays could prevent the loss of cell viability (viability remained around 100% for higher SPF) and the formation of lipid peroxides (30 to 80% reduction of peroxide levels). None of the two cell strains, submitted to UVB radiation, formed amounts of intracellular ROS in a dose-dependent manner. Under exposure to UVA radiation, only the HaCaT cell line produced the largest amounts of ROS in a dose-dependent manner. After treating these cells with photoprotective formulations (20 J/cm2), the researchers observed a reduction in the amount of ROS formed. Conclusions: The parameters of cell viability and lipid peroxidation were promising to evaluate the photoprotective capacity of sunscreens against UVB radiation. The generation of ROS expressed in the HaCaT strain can discriminate the photoprotective potential of formulations against UVA radiation, as sunscreens reduced the formation of ROS. These results suggest that in vitro tests that evaluate the damage caused to cells can predict cellular indicators of the photoprotective effectiveness of sunscreens and contribute to minimize these tests in the initial phase of product research and development.